Об асимтотической устойчивости нейронной сети на временной шкале - Лукьянова, Т.А.; Мартынюк, А.А. (Нелінійні коливання, 2010)
Отримано достатнi умови глобальної асимптотичної стiйкостi стану рiвноваги нейронної
системи на часовiй шкалi. Наведено новi достатнi умови регресивностi функцiї системи та
новi достатнi умови iснування та єдиностi стану рiвноваги нейронної системи. We obtain sufficient conditions for an equilibrium state of a neuron system to be globally asymptotically
stable in a time scale. New sufficient conditions for a system function to be regressive and new sufficient
conditions for existence and uniqueness of an equilibrium state of a neuron system are given.